PENGARUH HARGA DIRI TERHADAP PREFERENSI PEMILIHAN PASANGAN HIDUP PADA WANITA DEWASA AWAL YANG MENGALAMI QUARTER-LIFE CRISIS - Irma Rosalinda; Timothy Michael (Journal of Research and Measurement in Psychology, 2019)
This study aims to see the effect of self esteem towards mate selection preference in early adult women who experiencing quarter-life crisis. Participants in the study are 137 adult women aged 25 to 29 years old, working in Jakarta, single, and experiencing quarter-life crisis. The study used quantitative method and linear regression with one predictor. The measurement of self esteem using adopted instrument from Azwar, meanwhile for the measurement of mate selection using adapted instrument from Townsend and to screening the subjects who experiencing quarter-life crisis using adopted instrument from Agustin. The result show that there is an effect between self esteem on mate selection preference in early adult women who experiencing quarter-life crisis.